Role of Sugar Industry in Rural Development: A Case Study of Kushinagar District, U.P. - Tiwari, Anil Kumar; Pandey, R. K.; Sharma, V. N. (National Geographical Journal of India, 2022)
The agro-based industries have great significance in the Indian economy, where agriculture accounts for over 35 percent of the national income and about two third of the working population are engaged in agriculture. It is also noticeable that over three-fourths of Indian population lives in rural area who eed to upgrade their standard of living. Agro-based industries play an important role in strengthening industrial and agricultural linkages. In reference to eastern Uttar Pradesh, sugar industry is a major agro-based industry that plays a dominant role in rural development mostly in tarai region including Kushinagar district. This district has highest number of sugar mills, gur and khandsari units. Sugar industry used raw materials from agriculture and their output has markets in rural and as well as urban areas along-with international markets. Surplus rural manpower can be absorbed by these industries in this district. This industry provides an excellent nexus in promoting integrated development of agricultural and industry and in transforming a stagnant rural economy into a dynamic one in this area. Present study is an attempt to examine the role of sugar industry in rural development with the help of sample study of some selected nearby villages of sugar mills in Kushinagar district.